Philosophical and Aesthetic Components of the Art of the Baroque Style - E. V. Pozdnyakov (Vestnik MGIMO-Universiteta)
In this paper considers the impact of the historical process of the formation of the Counter- Reformation in the philosophical views of aesthetic expression, symbolism and personification of the Christian temple art of the Baroque